Phenytoin half-life and clearance during maintenance therapy in adults and elderly patients with epilepsy - Ahn, J E; Cloyd, J C; Brundage, R C; Marino, S E; Conway, J M; Ramsay, R E; White, J R; Musib, L C; Rarick, J O; Birnbaum, A K; Leppik, I E (Neurology, 2008)
Phenytoin (PHT) is widely used to treat epilepsy in elderly patients, but information on its pharmacokinetics in this population is limited. The purpose of this study was to investigate the effects of age and sex on PHT pharmacokinetics using stable-labeled (SL) isotopes of PHT or fosphenytoin (FOS) administered IV or IM while patients remained on their oral maintenance regimen. Subjects were patients 18 years or older with epilepsy, but otherwise healthy, on a maintenance regimen of PHT who were not taking interacting medications. Subjects were given a single injection of a 100 mg dose of SL-PHT or SL-FOS followed by their usual morning PHT dose less 100 mg. Serial blood samples were collected up to 196 hours after the SL dose. Plasma PHT and SL-PHT concentrations were measured by a gas chromatographic-mass spectrometric assay. PHT pharmacokinetics were characterized using a population-based, nonlinear, mixed-effects model. Sixty-three subjects completed the study, 45 of whom were 65 years or older. There was no difference between adult and elderly or men and women in PHT clearance, distribution volume, and elimination half-life. The mean elimination half-life was 40 hours. Healthy elderly adults appear to have the same phenytoin (PHT) pharmacokinetics as younger adults. Reduced PHT dosage requirements may be due to age-related changes in patients' sensitivity to the therapeutic and toxic effects of the drug. The prolonged elimination half-life suggests that most patients can take PHT once daily and the time to reach steady-state may extend to 2-3 weeks.